Effect Of Vegetable Waste Feed On Protein Levels Of BSF Maggots (Hermetia illucens) - Sitorus, Jernia Rulintan; Nursaadah, Euis; Primair Yani, Ariefa; Parlindungan, Deni; Hakim, Lukmanul (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: A BSF maggot (Hermetia illucens) is an organism that can live in waste media because maggots eat and decompose organic materials or waste for their growth. One innovative way to break down several types of organic waste, including vegetable waste, is to use maggots. This research aimed to analyze the effect of vegetable waste feed on maggots’ mass, length, thickness, and protein content. Methods: This research experimented with a completely randomized design (CRD) with five treatments, three repetitions of each treatment with various feed varieties. Analysis of maggot protein levels using the Automatic Kjeldahl method. The parameters measured were the maggot’s mass, length, thickness, and protein content. The variable in this research is the experimental variable for maggot samples with variations in the types of cabbage and mustard greens waste food. The number of samples used was 30 samples for each treatment. The data were analyzed using ANOVA, and a further BNT test was carried out to determine the natural effect of each treatment. Results: The results of the BNT and protein content test show that vegetable waste food significantly impacts the mass, length, thickness, and protein content of maggots. Conclusion: Feeding vegetable waste affects maggots’ mass, length, thickness, and protein content.